Fauna in The Creation Week by Wacław Potocki - Głuszak, Patrycja Katarzyna (The Motifs of Fauna and Flora in Literature and Culture, 2018)
The article is a study of the historical and literary background, as well as the encyclopedism of an early poem by Wacław Potocki, Tydzień stworzenia świata (The Creation Week). The author of the article discusses the classification of various animal species found in the poem and, basing on examples from the poem, shows the zoological prowess of the baroque poet, who ascribes various traits and properties to the creatures. The essay concludes with a proposal that curiositas (Latin for curiosities) present in the poem serve as an expression of Hexameron’s central truth — “God made the wild animals according to their kinds, the livestock according to their kinds, and all the creatures that move along the ground according to their kinds. And God saw that it was good” (Genesis 1:24– 25).